Ways of escape - Greene, Graham, 1904-1991 (Simon and Schuster, 1980)
With superb skill and feeling, Graham greene retraces the experiences and encounters of a long and extraordinary life. His restlessness is legendary; he has travelled like an explorer seeking our people and political situations. 'at the dangerous edge of things' - Haiti during the nightmare rule of Papa Doc, Vietnam in the last days - of the French. , Cuba, Prague, Paraguay, Kenya during the Mau Mau rebellion. With ironic delight he recalls his time in the British Secret Service in Africa, and his brief involvement in Hollywood. He writes, as only he can about people and places, about faith, doubt, fear and, not least, the trials and craft of writing.